2022
DOI: 10.1021/acscatal.2c00570
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Electrocatalysts in the Development of Gigawatt-Scale PEM Electrolyzers

Abstract: Electrocatalysts are nanomaterials of paramount importance within water electrolyzers, because they facilitate the electron transfer between reactants and electrode, enabling the chemical transformation of water into hydrogen and oxygen. In this Perspective, recent findings in electrocatalyst development for the next generation of polymer electrolyte membrane (PEM) water electrolyzers at scale are discussed. We discuss opportunities to create catalyst architectures, the importance to demonstrate electrode manu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 68 publications
0
32
0
Order By: Relevance
“…[1][2][3] The development of many advanced energy-conversion technologies, such as rechargeable metal air cells, regenerative fuel cells, and water splitting devices, rely heavily on the exploration of catalytic materials involved in these electrochemical processes and related performance enhancements, such as hydrogen evolution reaction (HER) and oxygen evolution reaction (OER). [4][5][6][7][8] However, most excellent electrocatalysts at present are Pt-based materials for HER, and Ir-or Ru-based materials for OER, all belonging to precious metals, which cannot be effectively used in industrialization due to their limited storage and high cost. 9,10 Various 3d-transition metal-based compounds have been gradually developed to replace these precious catalysts, and their electrocatalytic performances have been able to approach or even surpass that of the current precious metal system catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] The development of many advanced energy-conversion technologies, such as rechargeable metal air cells, regenerative fuel cells, and water splitting devices, rely heavily on the exploration of catalytic materials involved in these electrochemical processes and related performance enhancements, such as hydrogen evolution reaction (HER) and oxygen evolution reaction (OER). [4][5][6][7][8] However, most excellent electrocatalysts at present are Pt-based materials for HER, and Ir-or Ru-based materials for OER, all belonging to precious metals, which cannot be effectively used in industrialization due to their limited storage and high cost. 9,10 Various 3d-transition metal-based compounds have been gradually developed to replace these precious catalysts, and their electrocatalytic performances have been able to approach or even surpass that of the current precious metal system catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…However, large loadings of iridium-based catalysts (>1 mg Ir cm −2 ) are typically required to achieve long-term operation with minimal voltage losses, decreasing the scalability of electrolyzers and increasing cell manufacturing capital costs. 3,21 Recent power efficiency estimates have indicated that a 10-fold improvement in the performance of iridium-based catalyst layers is required for the scalable deployment of PEM-based electrolyzers. 21 As such, developing efficient and stable anode catalyst layers with limited iridium use is critical to meet these demands.…”
Section: Introductionmentioning
confidence: 99%
“…This design can produce hydrogen devoid of carbon emissions, which in turn can be coupled to carbon-capture technologies to produce synthetic precursors from atmospheric carbon dioxide, used as a fuel directly to provide heat or electrical power, or be utilized for ammonia production. Further, with the recent decline in renewable energy prices, the increased renewable energy capacity globally, and recent global mandates to develop a hydrogen-based economy, implementation of cost-effective water electrolyzers for green hydrogen is becoming more of a reality. , …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations